Edukasi Internet Sehat Untuk Anak Yatim Dan Dhuafa Pondok Pesantren Amanatul Huda - Hasugian, Humisar; Wulandari; Nofiyani; Anggoro, Dani (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Advances in information technology and the internet have had a significant impact on the lives of children, including orphans and the underprivileged. The internet is not only used for entertainment but also as a source of information that supports the learning process. However, internet use without adequate understanding and guidance can pose various risks, such as exposure to age-inappropriate content, discussing social media, and threats to the security and privacy of personal data. This activity was carried out with the aim of providing education on how to use the internet healthily to orphans and underprivileged children at the Amanatul Huda Islamic Boarding School. The implementation method was carried out through the stages of situation analysis, material preparation, training, and evaluation, using an interactive lecture approach, discussion, and direct practice of computer and internet use. The results of this activity were that participants had a better knowledge and understanding of how to use the internet safely and responsibly. Participants became more aware of the benefits of the internet for learning, recognized potential digital risks, and the importance of maintaining ethics and privacy while using the internet. This activity is expected to encourage positive internet use and be the first step in building a healthy digital literacy culture in the Islamic boarding school environment.